The A-Z of the PhD Trajectory - Eva, O.; Lantsoght, L. (Springer, 2018)
In this book, you can find information about the major milestones in your PhD trajectory, and how to reach them. We also discuss the soft skills that support the research process. This book is mostly aimed at PhD students in sciences and engineering. In particular, the topics that are discussed in this book are: defining your research question, developing a literature review, preparing and executing experiments, time management, scientific writing, academic presentations, and preparing for a career after the PhD.
A Practical Guide for a Successful Journey